2012
DOI: 10.1016/j.molcel.2012.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Live Cell Imaging Reveals a Gradual Shift between DNA Repair Mechanisms and a Maximal Use of HR in Mid S Phase

Abstract: Summary DNA double strand breaks are repaired by two main pathways: non-homologous end joining (NHEJ) and homologous recombination (HR). The choice between these pathways depends on cell cycle phase; however the continuous effect of cell cycle on the balance between them is still unclear. We used live cell imaging and fluorescent reporters for 53BP1, Rad52 and cell cycle to quantify the relative contribution of NHEJ and HR at different points of the cell cycle in single cells. We found that NHEJ is the dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
279
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(302 citation statements)
references
References 45 publications
14
279
2
2
Order By: Relevance
“…1A). These findings are in good agreement with data from other labs showing that even in G2, the vast majority (roughly 85%) of irradiation or drugs induced DSBs are repaired by NHEJ, 10,27 since active genes and H3K36me3 enriched loci represent only a minor fraction (few percent) of the genome. 28 Studies in yeast have confirmed that Set2, the SETD2 homolog, also plays a key role in DNA repair pathway choice but in this case, Set2 favored NHEJ over HR.…”
Section: Function Of H3k36me3 In Dsb Repair Pathway Choicesupporting
confidence: 92%
“…1A). These findings are in good agreement with data from other labs showing that even in G2, the vast majority (roughly 85%) of irradiation or drugs induced DSBs are repaired by NHEJ, 10,27 since active genes and H3K36me3 enriched loci represent only a minor fraction (few percent) of the genome. 28 Studies in yeast have confirmed that Set2, the SETD2 homolog, also plays a key role in DNA repair pathway choice but in this case, Set2 favored NHEJ over HR.…”
Section: Function Of H3k36me3 In Dsb Repair Pathway Choicesupporting
confidence: 92%
“…However, since the synchronization method used for ChIP analysis was serum starvation and release for ~10 h [ 24 ], we performed a longer time course analysis and found that some of cells in late G1 phase did begin to accumulate cohesin at DNA damage sites (data not shown). This is consistent with a gradual shift from NHEJ to HR during the G1-S transition, and some DSBs induced in late G1 can be repaired by HR as cells progress into S phase [ 30 ]. Thus, it is plausible that the "G1" ChIP signal of cohesin at damage sites might have been skewed by the subpopulation of cells in late G1 phase.…”
Section: Cohesin Promotes Sister Chromatid Hr and Suppresses Nhej Andsupporting
confidence: 69%
“…This might be explained by the refined activity profiles of NHEJ and HDR. 2 While we did not investigate off-target effects, a previous study could show that reduced dosages of Cas9 and sgRNA could reduce off-target modifications. 6 However, another study found that reducing expression levels of sgRNA and Cas9 in cells is not likely to provide a simple solution for reducing offtarget effects.…”
mentioning
confidence: 96%
“…In G2, DSBs are almost entirely repaired by NHEJ. 2 Consequently, the NHEJ pathway is largely favored over HDR in unsynchronized cell populations. This makes it difficult to introduce well-defined genomic alterations, e.g.…”
mentioning
confidence: 99%